Relationship between Serum Levels of OPG and TGF-β with Decreasing Rate of BMD in Native Chinese Women - Xi-Yu Wu; Yi-Qun Peng; Hong Zhang; Hui Xie; Zhi-Feng Sheng; Xiang-Hang Luo; Ru-Chun Dai; Hou-De Zhou; Xian-Ping Wu; Er-Yuan Liao (International Journal of Endocrinology)
The objective of this study was to investigate the relationship between serum levels of OPG, TGF-β1, and TGF-β2 and BMD decrease rate (BDR) in native Chinese women. This cross-sectional study was performed on 465 healthy native Chinese women aged 35–80 years. Serum levels of OPG, TGF-β1, and TGF-β2 were determined. BDR was measured by DXA at the posteroanterior spine, hip, and distal forearm. At all skeletal sites tested, there was a negative correlation between BDR and serum levels of both OPG (r=−0.122 to –0.230, all P = 0.007–0.000) and TGF-β2 (r=−0.100 to –0.173, all P = 0.029–0.000) and a positive correlation between BDR and serum TGF-β1 (r=0.245−0.365, all P=0.000). After adjustment for age and BMI, there were no statistically significant correlations between serum levels of OPG or TGF-β2 and BDR. However, statistically significant correlations between serum TGF-β1 and BDR at the lumbar spine and ultradistal forearm remained. Multiple linear regression stepwise analysis showed that serum OPG could explain 1.4–3.7% of BDR variation. Serum TGF-β1 was a positive determinant of BDR and could explain 5.3–13.3% of BDR variation.